What drives trade-related R&D Spillovers? Decomposing knowlege-diffusing trade flows - Jürgen Bitzer; Ingo Geishecker (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2005)
Our paper decomposes knowledge-diffusing trade flows and estimates their impacts separately. Overall, trade generates positive knowledge spillovers, but the effects of intra-industry trade are ambiguous. With regard to sectoral import penetration, we find that potential positive spillovers are dominated by negative competition effects. This, however, masks the significant positive spillover effects of intra-industry trade that corresponds to international out-sourcing.
Keywords: F20; O30; O40; D62; 330; R&D; trade; productivity; spillovers; competition; Industrielle Forschung; Spillover-Effekt; Produktivität; Intraindustrieller Handel; Wettbewerb; Schätzung; OECD-Staaten